Technical aspects of paediatric robotic pancreatic enucleation based on a case of an insulinoma. Issue 6 (11th August 2021) - Schulte am Esch, Jan; Krüger, Martin; Barthlen, Winfried; Förster, Christine; Mohnike, Konrad; Empting, Susann; Benhidjeb, Tahar; Vossschulte, Hendrik
Abstract: Background: Insulinomas are rare insulin‐producing pancreatic neuroendocrine tumours leading to severe episodes of hypoglycaemia. Surgery is the predominant curative therapy. Methods: We report here the first paediatric case of an insulinoma of the pancreatic body resected completely robotically under ultrasound guidance in a 10‐year‐old male with multiple endocrine neoplasia type 1. The port set‐up was adapted for the narrowed dimensions of the paediatric peritoneal space. We comment on technical key steps for the organ‐preserving procedure that was performed in close proximity to critical anatomic structures, with supporting video. Preoperative diagnostics, including endoscopic ultrasound, to determine surgical management are highlighted. Results: Following an uneventful post‐operative course, the boy was discharged on day 11 with normalised glucose‐metabolism. A pseudocyst developing after 4 weeks was treated with endoscopic stenting. Conclusions: The applicability of a robotic surgical system in limited space conditions such as found in the paediatric abdominal cavity is demonstrated here for pancreatic surgery.